Never never - Patterson, James, 1947-; Fox, Candice (2017)
Detective Harriet Blue of the Sydney Police Department prides herself on an uncanny ability to catch the most deviant of criminals. So when her brother is charged with a brutal string of murders, it rocks her world. Shocked, in denial, and facing uncomfortable questions about how much she knew, Harry is transferred to avoid the media circus. Investigating the disappearance of a worker in an isolated mine deep inside the desolate Australian outback--the never never--she uncovers an insular society that has sprung up around the mine. It's a world full of easy money, plenty of immoral ways to spend it, and no shortage of suspects. Still reeling from her investigative failures back home, Harry must get to the bottom of the mine's mysteries before she vanishes into the wilds of the never never for good
Recreational Reading Collection
Keywords: Suspense fiction; Women detectives -- Australia -- Sydney (N.S.W.) -- Fiction; Missing persons -- Fiction; Mines and mineral resources -- Fiction; Sydney (N.S.W.) -- Fiction